Simple Sukoba Artificial Intelligence (SSAI) – Movement - Melo, Arthur William Dórea; Araujo, Victor Flávio de Andrade (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Introduction: With the need of a new simple navigation and combat system for agents, the SSAI was created as a way to create a simple AI that can perform maneuvers procedurally such as ducking into cover, exposing to shoot, shooting and exploring. Objective: Create an in-house, customizable and simple AI system for shooting agent movement and shooting. Methodology or Steps: This article uses C#, Unity, raycasting and mathematics. Results: A functional, in-house, customizable and simple AI system for shooting agents in video games.